Water Scarcity : Impacts on Western Agriculture. - Engelbert, Ernest A. (University of California Press, 2022)
Agricultural production in the semi-arid western United States is dependent on irrigation. Population in the seventeen western states has been and is expected to continue increasing. Groundwater levels are declining throughout the region with long-term pumping and increased demands leading to greater pumping lifts and costs, land subsidence, and salt water intrusion into groundwater basins. Construction and operation costs of future water development in these.
Description based upon print version of record.
Keywords: Water-supply, Agricultural -- West (U.S.) -- Congresses.; Water-supply, Agricultural.; West United States.; Water-supply, Agricultural -- Congresses -- West (U.S.); landbouw met irrigatie; irrigated farming; watervoorziening; water supply; schaarste; scarcity; Agrohydrology; Agrohydrologie; Conference papers and proceedings.